حالی کی کتاب "مقدمۂ شعر وشاعری "میں مستعمل تنقیدی اصطلاحو ں کا تحقیقی وتنقیدی جائزہ - Hussain, Prof. Dr. Muzammil; Iqbal, Muhammad (Zoraiz, 2023)
Muqaddama e shair o shairi” by Altaf Hussain Hali is one of the books which can be called the first recognized book on criticism in Urdu. Before it, we have only sentences which give a hint of “Ta’assurati Tanqeed” (Expressional Criticism) in the context of fasahat o balaghat, ilme uruz, ilme qafia, but Hali took it seriously and theorized the discipline of criticism. He made use of the concepts of Western critics discipline of criticism. He made use of the concepts of Western critics like Milton and maintained the necessity of simplicity, ability and passion in poetry. Similarly he stressed the importance of imagination, the study of the universe and eloquence of words to achieve excellence in poetry. For this purpose, he made his point clear in “Muqaddama e Shair o Shairi” by using many current and new terms. This article will analyze these terms and trops used by Hali in this book in order to highlight the significance of this very first book on literary criticism in Urdu. Hali belonged to the Sir Sayyad school of thought. This school was founded on the purposeful literature. The terms used by Hali revolve around this thought, which accorded literature with the socio_ political and cultural consciousness of the age. Many of these terms are used frequently in Urdu, but Hali has given Urdu literary criticism a new dimension by imparting these terms new meanings. In this connection, it was quite essential to analyze these terms.